Worry-Free Database Upgrades: Automated Model-Driven Evolution of Schemas and Complex Mappings - Terwilliger, James; Bernstein, Phil; Unnithan, Adi (ACM SIGMOD, 2010)
Schema evolution is an unavoidable consequence of the application development lifecycle. The two primary schemas in an application, the client conceptual object model and the persistent database model, must co-evolve or risk quality, stability, and maintainability issues. We present MoDEF, an extension to Visual Studio that supports automatic evolution of object-relational mapping artifacts in the Microsoft Entity Framework. When starting with a valid mapping between client and store, MoDEF translates changes made to a client model into incremental changes to the store as an upgrade script, along with a new valid mapping to the new store. MoDEF mines the existing mapping for mapping patterns which MoDEF reuses for new client artifacts.